Barbier Continuous Flow Preparation and Reactions of Carbamoyllithiums for Nucleophilic Amidation. Issue 43 (17th July 2017) - Ganiek, Maximilian A.; Becker, Matthias R.; Berionni, Guillaume; Zipse, Hendrik; Knochel, Paul
Abstract: An ambient temperature continuous flow method for nucleophilic amidation and thioamidation is described. Deprotonation of formamides by lithium diisopropylamine (LDA) affords carbamoyllithium intermediates that are quenched in situ with various electrophiles such as ketones, allyl bromides, Weinreb and morpholino amides. The nature of the reactive lithium intermediates and the thermodynamics of the metalation were further investigated by ab initio calculations and kinetic experiments. Abstract : Hot chemistry at room temperature : An ambient temperature continuous flow method for nucleophilic amidation and thioamidation is described. Deprotonation of formamides in the presence of various electrophiles by lithium diisopropylamine (LDA) affords carbamoyllithium intermediates that are quenched in situ with various electrophiles. Insight into the thermodynamics of their metalation was gained by kinetic experiments an ab initio calculations.